Pathologizing populations and colonizing minds: internatioinal psychosocial programmes in Kosovo - Pupavac, Vanessa (Sage, 2002)
Through a case study of international responses in Kosovo, this article critically analyses how the international therapeutic model constructs war-affected populations as traumatised and subject to psychosocial dysfunctionalism. The international therapeutic model may be summarised as follows: traumatic experiences cause trauma symptoms producing low self esteem and dysfunctionalism leading to abuse/violence, requiring external intervention to break the cycle of trauma and violence. The first half of the paper contends the international projection of the population as traumatised. The second half of the paper examines psychosocial intervention as a new mode of external therapeutic governance. The paper suggests that concern for war trauma in international policy does not necessarily represent a positive development for war-affected populations. International psychosocial intervention has been criticised as a form of cultural imperialism, that is, the imposition of a Western therapeutic model on other societies, which have their own coping strategies.